Turf track surface interaction with speed and musculoskeletal injury risk in Thoroughbred racehorses - Legg KA; Gibson MJ; Gee EK; Rogers CW (John Wiley and Sons Ltd on behalf of EVJ Ltd, 2025)
Background: Injury modelling based on changes in speed and stride characteristics of racehorses has become a primary industry focus for the Thoroughbred racing industry. However, speed and stride characteristics are strongly associated with track condition; therefore, reliable quantification of surface variables for use in future models is imperative. Objectives: This study aimed to understand the interaction of objective turf track condition score (TCS) measurement with racing speed and injury in flat racing Thoroughbred horses. Study Design: Retrospective time series analysis. Methods: Race-day data from 16 flat racing seasons (2008/9–2023/24, n = 40,824 races) were used to compare monthly TCS (based on penetrometer measurements), the coefficient of variability (CV) for TCS, race speed (over the final 600 m) and the number of race starts. Injury data from 7 seasons (2015–17, 2019–24) were used to calculate the monthly incidence rate (IR per 1000 race starts) of musculoskeletal injury (MSI). A mixed effects linear model was used to assess the relationship between speed, TCS, race distance and horse rating. Results: Race starts (n = 437,506), TCS and speed showed strong seasonal fluctuations, with more starts, lower and more variable TCS (4, IQR 3–5, CV = 0.44) and higher race speed (16.7 m/s, IQR 16.1–17.2) in summer compared with winter (TCS 10, IQR 8–10, CV = 0.22, p < 0.001 and speed 15.1 m/s, IQR 14.3–15.8, p < 0.001). Race speed had a strong negative quadratic relationship with TCS (β₂ = −0.03, p < 0.001), a negative linear correlation with race distance and was positively correlated with horse rating. There were 433 MSI (IR = 2.22, 95% CI 2.20–2.44), with an immediate (0 lag time) positive association with seasonal changes in TCS (r = −0.28). Main Limitations: Low monthly numbers of MSI constrained analysis of interaction with track variables. Conclusions: TCS provides a reliable quantitative measure of track condition which could be used to refine future models of injury risk in racing Thoroughbreds.
Keywords: biomechanics; hoof–surface interaction; horse; penetrometer; turf track condition